Abhraka Bhasma (mica based nanomedicine): an ayurvedic herbomineral perspective in breast cancer management - Soman Pillai, Dhanya; Karavettekudy Ranjit, Amarnath (Frontiers in Pharmacology, 2025)
BackgroundAbhraka Bhasma (Mica nanoparticles) is an Ayurvedic herbomineral medicine traditionally used in the management of conditions similar to breast cancer. Its rationale is based on its Dhatu-Pushtikara (tissue-nourishing), Rasayana (rejuvenating) and Tridosha-balancing properties, suggesting its potential for evaluation in integrative oncology.ObjectiveThis work aims to examine the therapeutic potential of Mica nanoparticles (Abhraka Bhasma) as an alternative medicine in the management of breast cancer.Methods (type of evidence)This mini-review analyses the preclinical and limited clinical evidence supporting Abhraka Bhasma (mica nanoparticles) as a potential adjunct in breast cancer management. The mechanistic basis was evaluated from in vitro and in vivo models.Key findingsIn vitro: Abhraka Bhasma exhibits dose-dependent cytotoxicity, apoptosis, immunomodulatory activity and inhibition of teratoma-formation in different cell lines. In vivo: studies support these findings, indicating enhanced DNA repair capacity, reduced genotoxicity, chemopreventive responses, immunostimulatory effects and modulation of oxidative stress.ConclusionThe traditional Ayurvedic rationale for Abhraka Bhasma correlates with reported preclinical mechanisms. Thus, the ancient wisdom and modern evidence make Abhraka Bhasma an important part of integrative oncology, which offers a complementary strategy to improve patient outcomes. Available evidence on Abhraka Bhasma in cancer treatment is currently preclinical data (Level 5) and hypothesis generating only. To date, no RCTs or cohort studies (Levels 1–3) on the safety and efficacy of Abhraka Bhasma as an adjunct in breast cancer treatment have been published. To bridge the gap between traditional use and evidence based clinical application, a structured and systematic research pathway is essential.